Thermoregulatory responses of female buffaloes reared under direct sunlight and shaded areas in the dry season on Marajó Island, Brazil (Acta Scientiarum. Animal Sciences, 2018)
This research aimed to assess the effects of dry season climate variables on Marajó Island, Brazil, on the thermoregulatory responses of twenty female buffaloes, assigned to shaded (SD), and unshaded groups (US). Data on air temperature (AT), relative air humidity, wind velocity (WV), respiratory rate (RR), rectal temperature (RT), and body surface temperature (BST) were recorded at 6 a.m., 10 a.m., 2 p.m., 6 p.m., and 10 p.m. The temperature and humidity index (THI), practical buffalo comfort climatic conditions index (BCCCIp), and practical buffalo environmental comfort index (BECIp) were calculated. At 10 a.m. and 2 p.m., WV was the highest. The RR of animals in both treatments differed only at 10 a.m. and 2 p.m. A difference in RT between treatments was seen at 10 a.m., 2 a.m., and 6 p.m. Significant changes were seen in the BST of animals in both groups at 10 a.m., 2 p.m., and 10 p.m. BECIp was different between the groups at 10 a.m. and 2 p.m., with higher values for the US group. Buffaloes are prone to thermal stress, particularly between 10 a.m. and 2 p.m., when the highest values of AT, THI, and BCCCIp was observed.